The Relationship Between God Particles: Dark Matter and Time Dimensions - Chandri Maharani, Fareza; Aulia, Maulidatul; Maharani, Fareza Chandri; A’la, Dewi Ghitsatul (Journal of Biomedical and Techno Nanomaterials, 2024)
The God particle or Higgs Boson is a subatomic particle first proposed in 1964 and discovered in 2012 at CERN. It is an integral part of the Standard Model of Particle Physics, which explains the relationship between subatomic particles and the fundamental force. Dark Matter is hypothetical matter that interacts gravitationally with baryonic matter, but does not interact with the electromagnetic or strong and weak nuclear forces. Although invisible, dark matter is believed to make up the majority of matter in the universe. The Time Dimension is a dimension where objects move through time, indicating multiple points in space and time. In theoretical physics, the concepts of dark matter and the God Particle have been associated with additional dimensions of time. Some theories propose that additional time dimensions can be used to explain phenomena such as Dark Matter and the Higgs Boson. However, there has been no direct experimental evidence of additional time dimensions or how the God Particle and Dark Matter are related to additional time dimensions. In conclusion, the relationship between the God Particle, Dark Matter, and the Dimension of Time is still a topic of intense research in theoretical and experimental physics.